THE FINANCIAL STRATEGY OF THE ORGANIZATION AS A FACTOR OF ENSURING ECONOMIC SECURITY IN THE LONG TERM - Mansurov, Shahzod; Kochimova, Sevinch; Mukhtorov, Fazliddin (Science technology&Digital finance, 2023)
The article considers the issue of improving the financial strategy of the enterprise in terms of ensuring economic security, acting as a long-term planning tool.